Agatha Christie's Miss Marple. Volume one. A Caribbean mystery. The mirror cracked from side to side. [videorecording (DVD)] - Christie, Agatha, 1890-1976; Petit, Christopher; Stone, Norman; Hickson, Joan, 1906-1998; Pleasence, Donald; McKenna, T. P., 1929-2011; Bloom, Claire, 1931-; Newman, Barry, 1938-2023 (Miss Marple., 2001)
Prim and proper Miss Jane Marple uses her razor-sharp mind and intuitive understanding of criminal behavior to solve murder mysteries.